Effect of nutrition counselling with a digital job aid on child dietary diversity: Analysis of secondary outcomes from a cluster randomised controlled trial in rural Bangladesh - Billah, Sk Masum; Ferdous, Tarana E.; Kelly, Patrick; Raynes-Greenow, Camille; Siddique, Abu Bakkar; Gillespie, Stuart; Hoddinott, John F.; Menon, Purnima (Wiley, 2022)
Adequate dietary diversity among infants is often suboptimal in developing countries. We assessed the impact of nutrition counselling using a digital job aid on dietary diversity of children aged 6–23 months using data from a cluster randomised controlled trial in Bangladesh. The trial had five arms, each with 25 clusters. The four intervention arms provided counselling using a digital job aid and different prenatal and post-natal combinations of lipid-based supplements and the comparison arm with usual practice. We enrolled 1500 pregnant women and followed them until the children reached their second birthday. We developed a tablet-based system for intervention delivery, data collection and project supervision. We combined the four intervention arms (n = 855), in which community health workers (CHWs) provided age-appropriate complementary feeding counselling, to compare against the comparison arm (n = 403). We calculated the outcome indicators from the children's 24-h dietary recalls. Overall, the intervention increased the mean dietary diversity score by 0.09 (95% confidence interval [CI]: 0.2–0.16) and odds of minimum dietary diversity by 18% (95% CI: 0.99–1.40). However, there was a significant interaction on the effect of the intervention on dietary diversity by age. The mean dietary diversity score was 0.24 (95% CI: 0.11–0.37) higher in the intervention than in the comparison arm at 9 months and 0.14 (95% CI: 0.01–27) at 12 months of age. The intervention effect was non-significant at an older age. Overall, consumption of flesh food was 1.32 times higher in the intervention arm (odds ratio [OR] 1.32, 95% CI: 1.11–1.57) in 6–23 months of age. The intervention significantly improved child dietary diversity score in households with mild and moderate food insecurity by 0.27 (95% CI: 0.06–0.49) and 0.16 (0.05–27), respectively, but not with food-secure and severely food-insecure households. Although the study did not evaluate the impact of digital job aid alone, the findings indicate the utility of nutrition counselling by CHWs using a digital job aid to improve child feeding practices in broader programmes.